The spatial buildup of nonlinear compression in the cochlea - Kondylidis, Kostas; Vavakou, Anna; van der Heijden, Marcel (Frontiers in Cellular Neuroscience, 2025)
In the mammalian cochlea, the transduction from vibrations to inner hair cell receptor currents is preceded by a stage of mechanical pre-processing that involves a rapid, strongly nonlinear compression. The mechanisms by which the cochlea realizes this dynamic compression are still poorly understood. Previous work by our group suggested that compression does not occur locally, but is realized by a cascade of weakly nonlinear elements along the cochlear partition. The resulting progressive accumulation of nonlinearity was termed the spatial buildup of compression. Here we studied mechanical compression in the basal turn of the sensitive gerbil cochlea using optical coherence tomography. We recorded vibrations at multiple positions along the length of the cochlear partition. Such longitudinal studies were virtually impossible with previous techniques. Using a tailored two-tone stimulus we quantified the spatial profile of compression. We found that the amount of compression grew gradually in an intensity-dependent fashion along our measurement stretch, as we moved apically toward the place of maximum vibration. This gradual buildup of compression was not mirrored by a gradual reduction beyond the peak. In fact the amount of compression accumulated even beyond the peak. This asymmetric pattern supports the view that mechanical compression is realized in a cascaded, distributed fashion which hinges on the traveling wave nature of cochlear vibrations.